2011
DOI: 10.1002/asia.201100497
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Exocyclic Stereochemistry on the Tethered Aminohydroxylation Reaction

Abstract: A new strategy that employs an exocyclic stereocenter to effect diastereocontrol in the tethered aminohydroxylation (TA) reaction is applied to the stereoselective synthesis of a range of amino alcohols in good to excellent yields, and with anti selectivities of up to 20:1. The influence of the reaction conditions and substrate parameters on the level of diastereocontrol is described. Furthermore, an "inside alkoxy" model is employed to rationalize the sense and degree of stereoselectivity observed in these sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…33 Donohoe has also investigated the influence of exocyclic stereochemistry on the tethered aminohydroxylation reaction. 34 Meanwhile, the group of Luxenburger have prepared ethyl-, benzyl-, tert-butyl and fluorenylmethyl-4-chlorobenzoyloxycarbamates as storable, readily prepared nitrogen sources for the Sharpless aminohydroxylation reaction. 35 …”
Section: Alkene Aminohydroxylationmentioning
confidence: 99%
“…33 Donohoe has also investigated the influence of exocyclic stereochemistry on the tethered aminohydroxylation reaction. 34 Meanwhile, the group of Luxenburger have prepared ethyl-, benzyl-, tert-butyl and fluorenylmethyl-4-chlorobenzoyloxycarbamates as storable, readily prepared nitrogen sources for the Sharpless aminohydroxylation reaction. 35 …”
Section: Alkene Aminohydroxylationmentioning
confidence: 99%
“…More recently, stereocentres located outside of the hetereocycle formed in the reaction have been employed to induce diastereoselectivity in the TA reaction; consider the reaction of the bench stable aroyloxycarbamate precursors 29a-c (Scheme 9). [12] Scheme 9. Employing an exocyclic stereocentre to control the diastereoselectivity during the TA reaction.…”
Section: Reoxidants Based On Carbamatesmentioning
confidence: 99%
“…Several reports of diastereoselectivity in the intermolecular oxyamination reaction serve to highlight the potential of this element of stereocontrol for the synthesis of amino alcohol containing compounds, 4,13,14 including natural products. Several reports of diastereoselectivity in the intermolecular oxyamination reaction serve to highlight the potential of this element of stereocontrol for the synthesis of amino alcohol containing compounds, 4,13,14 including natural products.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of diastereoselectivity in the intermolecular oxyamination reaction serve to highlight the potential of this element of stereocontrol for the synthesis of amino alcohol containing compounds, 4,13,14 including natural products. 14 Herein we disclose a study on the diastereoselectivity of the osmium-catalyzed intermolecular vicinal oxyamination of acyclic allylic alcohol derivatives with benzyl N-(4-tosyloxy)carbamate (1, Scheme 1). Recently, a study reported the influence of exocyclic stereochemistry on the on the intramolecular osmium-catalyzed TA reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation